Emily’s Maternal Ideal: Pregnancy, Birth, and Resistance at Kingston Penitentiary - McCoy, Ted (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2016)
The 1850s and 1860s saw the rise of a new women’s prison reform ideology that would shape the next half-century of women’s imprisonment. “Maternalism” was the promotion of femininity as the basis of reform and rehabilitation with accompanying notions of ideal womanhood and appropriate roles for imprisoned women and in the aftermath of a penitentiary sentence. This paper looks at literal motherhood in the penitentiary by examining the experiences of prisoner Emily Boyle. Boyle was pregnant during two separate terms at Kingston Penitentiary. During the first term in 1926, she was paroled so that she could return to Edmonton to give birth. During her second term in 1932, no mercy was extended in consideration of her pregnancy and Boyle began a battle with the Department of Justice over her right to keep her baby within the walls of Kingston Penitentiary. The warden recommended that Boyle be separated from her child and it be sent to the Home for Infants, in spite of the fact that the father was in Edmonton. Boyle resisted this decision, and in fact resisted all penitentiary involvement with her pregnancy and childbirth. She ultimately gave birth in the bathroom of the women’s ward with the assistance of two matrons. When the child was taken away from her, both Boyle and her husband fought the Department of Justice decision on the matter, rallying against the notion that their child was better served by the Children’s Aid Society. The paper examines multiple questions about motherhood and maternalism in the penitentiary’s first century. It argues that maternalism and motherhood were found at cross purposes when balanced with the demands of punishment. Emily Boyle found herself at this intersection, fighting to keep her child in an institution geared towards teaching her to become the ideal mother.